Structural properties of cooperation networks in Germany: From basic to applied research - Tom Brökel; Holger Graf (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Economists pay more and more attention to knowledge networks and drivers of their development. Consequently, a rich literature emerged analyzing factors explaining the emergence of intra-organizational links. Despite substantial work focusing on the dyad level, only little is known about how and why (global) network structures differ between technologies or industries. The study is based on a new data source on subsidized R&D cooperation in Germany, which is presented in detail and discussed with respect to other types of relational data. A comparison of networks within ten technologies allows us to identify systematic differences between basic and applied research networks.
Keywords: L14; I28; O38; 330; R&D subsidies; network; cooperation; Foerderkatalog; Germany; Forschungskooperation; Forschungssubvention; Unternehmensnetzwerk; Technologie; Industrielle Forschung; Deutschland